Trendy versus Appropriate Language Use: The Position of Standard English in Formal Written and Spoken Communication among Undergraduates of Selected Universities in Abuja - Martha Nguemo Terna-Abah (International Journal of Social Sciences & Educational Studies, 2022)
This paper examines the prevalence of nonstandard English usage in formal communication among selected undergraduates and its implication on the Standard English. The paper begins by looking at the choice of appropriate English language variety suitable for any given context as one of the yardsticks for determining one’s competence in English language. It thereafter establishes the fact that younger English language users are increasingly finding it difficult to draw boundaries between when to use nonstandard English varieties which are popular among them and when to use the standard varieties considered appropriate in formal communication. Data was collected from students’ spoken and written communication. Using Fishman’s Domain and Topics as its theoretical framework, the paper analysed the data obtained against the contexts within which they were used and established that their use in those contexts was inappropriate. The work was able to also establish that these usages pose a threat to the Standard English and formal communication as they lead to ambiguity and loss of meaning which make comprehension difficult for the targeted audience. After discussing the way forward, the paper concludes by reiterating the fact that although the emerging variety of English prevalent among the youths is rich and interesting, its use in formal communication remains largely inappropriate.